2011
DOI: 10.1016/j.jviscsurg.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience using robot- assisted transaxillary thyroidectomy for Graves’ disease

Abstract: We showed that robotic transaxillary thyroidectomy is feasible and can be safe and effective in patients with Graves' disease. To our knowledge, this is the first article describing this approach for Graves' disease. These findings, however, warrant additional investigation within future prospective clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
(38 reference statements)
0
24
0
1
Order By: Relevance
“…The utility of a robotic surgical approach to the management of Graves thyroiditis is less clear as it was considered a contraindication for surgery in several of the initial clinical studies. Kandil et al [42] reported their findings on a group of five patients undergoing GTA with total thyroidectomy for Graves disease. They were successful in performing the procedure robotically and had no reported post-operative complications.…”
Section: Thyroiditismentioning
confidence: 99%
“…The utility of a robotic surgical approach to the management of Graves thyroiditis is less clear as it was considered a contraindication for surgery in several of the initial clinical studies. Kandil et al [42] reported their findings on a group of five patients undergoing GTA with total thyroidectomy for Graves disease. They were successful in performing the procedure robotically and had no reported post-operative complications.…”
Section: Thyroiditismentioning
confidence: 99%
“…Endoscopic approaches are not recommended due to difficulties in controlling bleeding [23,37]. In a series of 5 robotic subtotal thyroidectomies for Graves' disease, there were no conversions to open or endoscopic techniques and no postoperative complications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 5 robotic subtotal thyroidectomies for Graves' disease, there were no conversions to open or endoscopic techniques and no postoperative complications (e.g. bleeding, hypocalcemia and vocal cord palsy) [23]. Importantly, the case series cited lower intraoperative blood loss than with endoscopic and open techniques, attributed to the excellent surgical field view and precise movements when using the robot [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations